Understanding and contextualizing teen dating violence - Maria das Graças Carvalho Ferriani; Ana Beatriz Campeiz; José Eurípedes Martins; Ailton de Souza Aragão; Eliana Mendes de Souza Teixeira Roque; Diene Monique Carlos
Abstract Objective: To describe and analyze teen dating violence with adolescents of a public school in a city in the state of São Paulo. Method: Qualitative research, anchored by the Paradigm of Complexity. Data collection was carried out with 16 students of the 11st year of high school, through focus groups and semi-structured interviews. Data analysis was based on the thematic modality. Results: There emerged three themes, which made it possible to understand that the myth of romantic love has still present in intimate relationships; as an aspect of these myths, jealousy is revealed as inherent in relationships, while time triggering teen dating violence at the same. Digital social networks have been throughout this process; the family and the school emerge as contexts that expose adolescents to vulnerability, including the experience of other violence manifestations. Conclusion and implications for practice: Multidimensional, retroactive and interdependent nature of the aspects related to teen dating violence were identified. Promotion of healthy dating relationships from the deconstruction of romantic love myths; safe use of virtual social networks by adolescents; actions to promote healthy parenting and articulation of health-school-family, with the empowerment of these spaces as factors to protect violence involving adolescents are necessary.